A Systematic Review: Early Warning System for Hospital Wards - Sasmito, Priyo; Aljufri, Salim; Mulyati, Leli; Rasmita, Dina; Syafridawita, Yetti; Deviana, Elina; Komariah, Elis; Gayatri, Sri Wahyuni; Arifani, Nisa (International Journal of Public Health Excellence (IJPHE), 2024)
Most of the unexpected events occur in the hospital wards. An Early Warning System (EWS) is a system created to identify worsening patients outside the Intensive Care Unit (ICU). EWS is one of the requirements that must be met to get hospital accreditation. Hospitals have to choose the appropriate EWS to get optimal outcomes. This study aims to describe some of the EWS in the wards that have been researched and developed, as well as their performance in predicting severe adverse events (SAE). This study is a literature review design, conducting a systematic review by selecting relevant articles on Pub Med and Science Direct using the keyword "Early Warning Systems" in the 2018-2023 period. Out of 269 articles, only 12 articles that met the criteria. The selected articles are then systematically reviewed and analyzed. Based on the extraction results of 12 articles, 9 EWS were grouped into National Early Warning Score (NEWS) and its variants, Modified Early Warning Score (MEWS) and its variants, and EWS integrated with Electronic Medical Record (EMR). In choosing an EWS, hospitals must consider the complexity of the cases being managed and the capabilities of existing resources. The recommended EWS in hospital wards with limited resources is weighted EWS or EWS with combinations, such as NEWS and MEWS with variants. Meanwhile, hospitals that have used EMR can choose EWS integrated with EMR to increase their predictive value for SAE, as well as improve protocol compliance.